Masa Jabatan CEO, Keragaman Dewan Direktur, dan Pengungkapan CSR: Eksplorasi Studi Kepustakaan - Suham Cahyono; Tjiptohadi Sawarjuwono; Wendi Wendi (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
Purpose: This study reviews various literatures and obtains an overview of the relationship between a CEO's Tenure and Boards Diversity and the quality of Corporate Social Responsibility (CSR) disclosures.Method: The research method used in this study is a qualitative method, namely library research, by utilizing information sources derived from reputable online journals such as Scopus and Google Scholar as well as additional information obtained from articles, books, laws, and other documents relevant to the topic study.Results: The results of studies from various sources show that the quality of CSR disclosure is strongly influenced by the tenure of the CEO and also the diversity of the board of directors. Short CEO tenure tends to increase the quality of CSR disclosure. This is because the tenure is short, the CEO will try to optimize his tenure in order to increase the credibility and ability of the CEO to lead a company. On the other hand, a working tenure that is too long can reduce the quality of CSR report disclosure. The diversity of management also has strong implications for improving the quality of CSR report disclosure. The diversity of administrators can motivate the emergence of creative and innovative ideas to disclose better CSR reports.Implications: This research can be used as material for consideration for companies in making decisions in determining the tenure of the CEO and the diversity of the board.Novelty: This study is the first study attempt by doing research qualitative with considering many previous studies to make some conclusions and contribute to extant literature related to the corporate mechanism by doing library research.